Constructal design of subcooled microchannel heat exchangers - Ariyo, David O.; Bello-Ochende, Tunde (International journal of heat and mass transfer, 2020)
•Subcooled flow boiling in optimized rectangular microchannels is presented.•Eulerian multiphase model in ANSYS which was used for the simulations is presented.•Optimization program with search algorithm was used to obtain optimized geometric and flow parameters.•High thermal performance of the optimized microchannels was observed for the ranges of heat flux and velocity.•Low pumping power was observed for the optimized microchannels. This paper presents geometric optimization and flow parameters modelling for subcooled flow boiling (two-phase flow). The objective of the paper was to minimize the thermal resistance of the microchannel heat exchanger subject to fixed volume constraints of heat sink and microchannel. The geometric and flow parameters were allowed to morph, according to the constructal design principles to obtain their optimized values. The flow was highly subcooled at inlet temperature of 25 °C using deionized water as the cooling fluid and aluminium as the heat sink material. Velocities between 0.1 and 4.5 m/s and heat fluxes between 100 and 1200 W/cm2 (1 × 106 W/m2 and 1.2 × 107 W/m2) were used in the modelling and optimization. Computational fluid dynamics code, ANSYS was used for both the simulations and the optimization of the configurations. The numerical code used for the simulations was validated by available experimental data in the literature and the agreement showed the capability of CFD (ANSYS) to predict accurately, subcooled flow boiling (two-phase flow) in rectangular microchannel heat exchangers for cooling of microelectronic devices. Comparisons were made between two-phase flow and single-phase flow by using their optimized geometric and flow parameters, and the results clearly demonstrated the superiority of two-phase flow regime in rectangular microchannels for removal of high heat fluxes at low Reynolds numbers. As the optimized Reynolds number increases, the minimized thermal resistance (peak temperature) decreases which is consistent with previous results obtained in the open literature. Results further show the aspect ratio, the optimized diameter and axial length of the microchannel as a function of the dimensionless pressure drop number (Bejan number).